2020 American Community Survey: Use with Caution, An Analysis of the Undercount in the 2020 ACS Data Used to Derive Estimates of the Undocumented Population. (June 2022) - Warren, Robert
This paper analyzes and provides estimates of the undercount of the foreign-born in the US Census Bureau's 2020 American Community Survey (ACS). It confirms that a differential undercount occurred in the 2020 ACS. In particular, noncitizens that arrived from Central American countries after 1981 had undercount rates of 15–25 percent, but undercount of noncitizens that arrived from European countries in the same period was not detectable by the methods described in this paper. The Center for Migration Studies of New York (CMS) and others use ACS data to derive annual estimates of the US undocumented population. The Census Bureau recently reported that the total population count for the 2020 Census was consistent with the count for recent censuses, despite the Covid-19 pandemic and the Trump administration's interference in the 2020 Census. Nonetheless, the accuracy of 2020 ACS data for the noncitizen population that arrived after 1981 remains a major concern given the fear generated by the Trump administration's abusive rhetoric and anti-immigrant policies. The estimates set forth in this paper were derived by analyzing trends in annual ACS data for 2016–2020 compiled from the IPUMS website (Ruggles et al. 2021). Decennial census data cannot be used for this purpose because data on country of birth, citizenship, and year of immigration are not collected in the census. However, it is reasonable to believe that the 2020 census and the 2020 ACS experienced similar challenges because they were conducted under comparable conditions. The patterns of undercount of noncitizens described here for the 2020 ACS are likely mirrored in the 2020 census and will reduce federal funding and representation to affected cities and states for the next decade.